Regenerative Medicine: Charting a New Course in Wound Healing - Gurtner, Geoffrey C. (Adv Wound Care (New Rochelle), 2016)
Significance: Chronic wounds are a prevalent and costly problem in the United States. Improved treatments are needed to heal these wounds and prevent serious complications such as infection and amputation. Recent Advances: In wound healing, as in other areas of medicine, technologies that have the potential to regenerate as opposed to repair tissue are gaining ground. These include customizable nanofiber matrices incorporating novel materials; a variety of autologous and allogeneic cell types at various stages of differentiation (e.g., pluripotent, terminally differentiated); peptides; proteins; small molecules; RNA inhibitors; and gene therapies. Critical Issues: Wound healing is a logical target for regenerative medicine due to the accessibility and structure of skin, the regenerative nature of healing, the lack of good limb salvage treatments, and the current use of cell therapies. However, more extensive knowledge of pathophysiologic targets is needed to inform regenerative strategies, and new technologies must demonstrate value in terms of outcomes and related health economic measures to achieve successful market access and penetration. Future Directions: Due to similarities in cell pathways and developmental mechanisms, regenerative technologies developed in one therapeutic area may be applicable to others. Approaches that proceed from human genomic or other big data sources to models are becoming increasingly common and will likely suggest novel therapeutic avenues. To fully capitalize on the advances in regenerative medicine, studies must demonstrate the value of new therapies in identified patient populations, and sponsors must work with regulatory agencies to develop appropriate dossiers supporting timely approval.